PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASIONAL PT PERKEBUNAN NUSANTARA XIII KANTOR DIREKSI - B2042131024, Nalsali Frisko Bangun FEB UNTAN (Equator Journal of Management and Entrepreneurship (EJME), 2019)
ABSTRACT This study aim to identify and provide empirical evidence about whether the variable Leadership style and Discipline Work on employee Performance through Organizational Commitment at PT Perkebunan Nusantara XIII Office Directors.This study using path analysis with SPSS 16. The population used is the employee who is on the board of directors of PT Perkebunan Nusantara XIII criteria Samples used as many as 125 employees of Directors of PT Perkebunan Nusantara XIII.The result of this study indicate that the Leadership Style are positive impact on employee performance and Discipline partially positive effect on employee performance and the effects of direct and indirect concluded that variable leadership style and Discipline would be better off without the employee performance through Organizational Commitment. Keywords : Leadership Style, Work Discipline, Organizational Commitment and Employee Performance